1992
DOI: 10.2307/3431332
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Eicosanoid Production by Human Alveolar Macrophages Exposed to Silica in Vitro

Abstract: Repeated inhalationofsiLca dt can lead to hlammatlonam fibrosin hun iun and ineperimtal anial mods. The alveolar macrophage is believed to play a pivotal role in this process. Numerous macrophage-derived growth factors, cytokines, and arachidonic acid metabolites have been shown to contribute to inflammation and fibrosis. The objective of this study was to determine the eicosanoid production by human alveolar macrophages in response to silica exposure in vitro andtoassess the contribution ofalveolar macrophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The silica particles did not influence the viability of cells, so there is probably not a toxic effect. In other studies silica particles have been shown to decrease secretion of two other substances, namely, thromboxane B 2 and prostaglandin E 2 (Brown et al, 1988;Koren et al, 1992). It should be of value to confirm these results with other insoluble particles.…”
Section: Discussionmentioning
confidence: 55%
“…The silica particles did not influence the viability of cells, so there is probably not a toxic effect. In other studies silica particles have been shown to decrease secretion of two other substances, namely, thromboxane B 2 and prostaglandin E 2 (Brown et al, 1988;Koren et al, 1992). It should be of value to confirm these results with other insoluble particles.…”
Section: Discussionmentioning
confidence: 55%
“…While both mediators are known to have chemotactic activities, LTB 4 stimulates the secretory response of inflammatory cells, whereas PGE 2 is considered to have downregulatory effects on inflammatory cell function [44]. There are a number of studies indicating that LTB 4 produced by AM is closely associated with the inflammatory response caused by inhalation of various particulates.…”
Section: Release Of Cytokines and Eicosanoidsmentioning
confidence: 99%
“…There are a number of studies indicating that LTB 4 produced by AM is closely associated with the inflammatory response caused by inhalation of various particulates. Koren et al [44] demonstrated an increased LTB 4 release by AM upon in vitro exposure to silica, asbestos fibers, and carbonyl iron. Others reported that asbestos fibers induced an enhanced release of PGE 2 as well as an increased LTB 4 production by AM in vitro [45,46].…”
Section: Release Of Cytokines and Eicosanoidsmentioning
confidence: 99%
“…Lipid mediators may play a major role in promoting or eliciting responses of lung tissue to air pollutants such as ozone (6,7), sulfurrelated species, especially sulfite (8,9), silica (10,11), and residual oil fly ash (12). Among the lipid mediators, platelet-activating factor and products of the 5-lipoxygenase (5-LO) pathway such as leukotriene B 4 (LTB 4 ) are known to stimulate immune cells such as polymorphonuclear neutrophil (PMNs) (13)(14)(15).…”
mentioning
confidence: 99%